Intergrasi media Pembelajaran Digital dan pemetaan Konsep Dalam Kemampuan Pemecahan masalah matematis: Systematic Literatur Review - Asma Aziza; Sukasno; Anna Fauziah (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to analyze the characteristics and trends in the use of digital learning media, examine the role of concept mapping strategies, and identify the potential integration of both in improving students' mathematical problem-solving abilities. The study employed a Systematic Literature Review (SLR) methodology following the PRISMA 2020 guidelines. Data sources were obtained through Google Scholar, focusing on articles indexed in Scopus Q1 and journals classified under SINTA 2 and SINTA 3. From the initial search results, a total of 48 articles were identified, of which 20 met the established inclusion criteria. The findings indicate that digital learning media are characterized by interactivity, flexibility, and their capacity to effectively visualize abstract mathematical concepts. Concept Mapping strategies were found to assist students in organizing knowledge and understanding relationships among concepts. Furthermore, the integration of digital educational resources and concept mapping demonstrates significant potential for enhancing mathematical problem-solving competence. These findings suggest that the combination of technological tools and cognitive methodologies can serve as an effective alternative for improving the quality of mathematics education.